Physical development of the corps de ballet in Poznań opera-house - Gajewska-Stańda, Alicja (Anthropological Review, 1974)
The stature and weight of the best professionally active dancers in the ballet company at the Opera-house in Poznań were analysed. The studied corps de ballet in comparison with other groups that cultivate various sport activities is characterized of an average high stature and light weight and that gives them a slender silhouette.